Small Mars Mission Architecture Study - Claire E. Parfitt; Adam G. McSweeney; Lisa De Backer; Csilla Orgel; Andrew J. Ball; Michael Khan; Sanjay Vijendran (Advances in Astronomy)
While the vast majority of ESA’s funding for Mars exploration in the 2020s is planned to be invested in ExoMars and Mars Sample Return, there is an interest to assess the possibility of implementing a small mission to Mars in parallel with, or soon after, the completion of the MSR programme. A study was undertaken in the Concurrent Design Facility at ESA ESTEC to assess low-cost mission architectures for small satellite missions to Mars. Given strict programmatic constraints, the focus of the study was on a low-cost (<250MEuro Cost at Completion), short mission development schedule with a cost-driven spacecraft design and mission architecture. The study concluded that small, low-cost Mars missions are technically feasible for launch within the decade.